Isolation of Mitochondria From Fresh Mice Lung Tissue - Caldeira, Dayene de Assis Fernandes; Oliveira, Dahienne Ferreira de; Cavalcanti-de-Albuquerque, João Paulo; Nascimento, Jose Hamilton Matheus; Zin, Walter Araujo; Maciel, Leonardo (Frontiers in Physiology, 2021)
Direct analysis of isolated mitochondria enables a better understanding of lung dysfunction. Despite well-defined mitochondrial isolation protocols applicable to other tissues, such as the brain, kidney, heart, and liver, a robust and reproductive protocol has not yet been advanced for the lung. We describe a protocol for the isolation of mitochondria from lung tissue aiming for functional analyses of mitochondrial O2 consumption, transmembrane potential, reactive oxygen species (ROS) formation, ATP production, and swelling. We compared our protocol to that used for heart mitochondrial function that is well-established in the literature, and achieved similar results.